Lots, feeding-places, houses and fences for hogs - Thompson, Carl (My University, 1904)
Introduction: The subject of, caring for the hogs, is perhaps one of the most important questions that confronts the farmer today. And yet the average farmer gives it but little thought. It has long been known that hog raising is one of the most important industries on the farm, but very few people seem to think that any reasonable care is needed to make a success of it. Men build barns for their horses, sheds and stables for their cows and houses for their poultry, but as for the hogs the general impression is - "Oh they are nothing but hogs they need no special care". And so it goes, The hog gets his feed and water when it is convenient for, the farmer to wait upon him, and he is, as a rule, allowed to seek shelter where he may. But the time is now at hand when it takes skill and care to produce money by the raising of hogs the same as in any other industry on the farm, and the time is nigh at hand when the hog shall receive the care and treatment that he has so long deserved.
Citation: Thompson, Carl. Lots, feeding-places, houses and fences for hogs. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Hogs; Livestock; Livestock Shelters; Animal Rights; Tending Livestock; Theses